Ornithodoros quilinensis sp. nov. (Acari, Argasidae), a new tick species from the Chacoan region in Argentina - Venzal, José Manuel; Nava, Santiago; Mangold, Atilio Jose; Mastropaolo, Mariano; Casás, Gustavo; Guglielmone, Alberto (Springer, 2019)
Ornithodoros quilinensis sp. nov. (Acari: Argasidae) is described from larvae collected on the small rodents Graomys centralis (Cricetidae: Sigmodontinae) in Argentina. The diagnostic characters for this new species are a combination of small size (520–540 μm), a dorsal plate oval in shape with a length of approximately 200 μm, 14 pairs of dorsal setae, hypostome short and narrower at the base (length from Ph1 to apex 133 μm (120–141)) with dental formula 2/2 and apex blunt, and the capsule of the Haller’s organ irregular in shape and without reticulations. The analysis of the 16S rDNA sequences available for the genus Ornithodoros indicate that, phylogenetically, O. quilinensis represents an independent lineage only related to a Bolivian tick species of the genus Ornithodoros yet not formally described.